'Raising a moral generation': the Republican People's Party and religious instruction in Turkey, 1946–1949. Issue 3 (4th May 2017) - Bilgiç, Tuba Ünlü; Bilgiç, Bestami S.
ABSTRACT: When Recep Tayyip Erdoğan, as the Prime Minister of the Turkish Republic, declared his government's intention to raise a 'religious generation', his proposition drew harsh criticisms from Turkey's secularists, who argued that doing so would clearly challenge the secular nature of the Turkish state. Yet it may come as a surprise to many that it was not a conservative party with Islamist leanings that first experimented with the idea of relying on religious education as an antidote to the perceived moral decadence of the society. Rather, it was the secularist party, the Republican People's Party, which attempted to use religious instruction for the same purpose during the heyday of Kemalism in the 1940s. Against this backdrop, providing an analysis of how the Republican People's Party had come to the point of offering religious education to school children and how it justified this policy can shed light on today's debate on secularism and the secular character of the Turkish state.